FORECASTING OF STATES OF THE SAME TYPE OF LOCOMOTIVE FLEET (VL8) OF PRIDNEPROVSKA RAILWAY - Lahuta, V. V.; Kapitsa, M. I. (Science and Transport Progress, 2004)
The article considers prognostication of the stationary mode of the fleet of VL8 locomotives on the basis of Kolmogorov′s equations of the mass service theory and optimization task, with the use of observation data.